Correlation of spectral variables and aboveground carbon stock of agroforestry systems - Bolfe, Édson Luis; Batistella, Mateus; Ferreira, Marcos César (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the correlation between spectral variables and aboveground carbon stock of agroforestry systems in the region of Tomé‑Açu, PA, Brazil. Twenty‑four vegetation indices from three groups (simple ratio, normalized difference, and complex), calculated from images of the TM/Landsat‑5 sensor acquired in 2008, were tested. The obtained variables were correlated, by means of simple linear regression, to carbon stock from four agroforestry systems with different ages and floristic composition. The correlations obtained among spectral variables and carbon stock were significant in 47% of the tested indices and changed according to the differences in biomass of the analyzed systems. The best correlations were obtained by the simple ratio and normalized difference indices in young agroforestry systems, and by complex vegetation indices in older agroforestry systems.